Case study: risperidone-induced hepatotoxicity in pediatric patients - Kumra, S; Herion, D; Jacobsen, L K; Briguglia, C; Grothe, D (Journal of the American Academy of Child and Adolescent Psychiatry, 1997)
The purpose of this case study is to document hepatic adverse effects associated with long-term risperidone use in pediatric populations. Charts of all patients admitted to the National Institute of Mental Health (NIMH) from December 1993 to April 1996 who had been treated with risperidone were screened for hepatotoxicity and weight gain. From the medical records of 13 psychotic children admitted to the NIMH and treated with risperidone, 2 children (both male) who presented with obesity, liver enzyme abnormalities, and confirmatory evidence of fatty liver were identified. In each case liver damage was reversed after discontinuation of risperidone and/or associated weight loss. The observations suggest that long-term risperidone therapy is possibly associated with hepatotoxicity in male pediatric patients. It is recommended that pediatric patients treated with risperidone have baseline liver function tests, careful monitoring of weight, and periodic monitoring of liver function tests during the maintenance phase of therapy.